The construction of road diversion in swampy area ta Jalan Lencongan Kurong Tengah, Perlis - Md. Nasir, Noor Izaidah (2013)
There are many road projects being implemented in Malaysia. Since Malaysia is developing fast, new technology are constantly being used either in building or road construction. However, some of the terrain in Peninsular Malaysia differs from each other. One of the challenges faced in road projects are the construction of roads in swampy areas. The engineers will have to use their skills and experience in order to construct the roads in swampy areas. The aim of this study is to assess the road construction method in swampy areas and the problems faced by the contractors in carrying out the construction works. The objectives of the study are to study the methods used for road construction in swampy area, to identify the factors taken into consideration for the construction of road diversion, to identify the problems faced by the contractor in construction of the road diversion in swampy area and to evaluate the factors that influence the duration of the project for construction of road in swampy area. This is a case study and the data are collected through questionnaires and interviews. The data is analyzed using statistical analysis and average index. From the study, the construction of road in swampy areas involves removal and replacement of soil, construction of prefabricated vertical drain and by surcharge. The factors taken into consideration in constructing roads over swampy areas are the safety factor in the design, location of site area and the life span of the method used. The problems faced by the contractor in road construction in swampy areas are soil treatment, weather and high ground water table. The factors that influence the duration of completion of the project are design changes, difficult to estimate time as they are influence by the type of soil problems and unexpected weather.